A Novel, Stable, Aqueous Glucagon Formulation Using Ferulic Acid as an Excipient. (24th September 2014) - Bakhtiani, Parkash A.; Caputo, Nicholas; Castle, Jessica R.; El Youssef, Joseph; Carroll, Julie M.; David, Larry L.; Roberts, Charles T.; Ward, W. Kenneth
Background: Commercial glucagon is unstable due to aggregation and degradation. In closed-loop studies, it must be reconstituted frequently. For use in a portable pump for 3 days, a more stable preparation is required. At alkaline pH, curcumin inhibited glucagon aggregation. However, curcumin is not sufficiently stable for long-term use. Here, we evaluated ferulic acid, a stable breakdown product of curcumin, for its ability to stabilize glucagon. Methods: Ferulic acid-formulated glucagon (FAFG), composed of ferulic acid, glucagon, L-methionine, polysorbate-80, and human serum albumin in glycine buffer at pH 9, was aged for 7 days at 37°C. Glucagon aggregation was assessed by transmission electron microscopy (TEM) and degradation by high-performance liquid chromatography (HPLC). A cell-based protein kinase A (PKA) assay was used to assess in vitro bioactivity. Pharmacodynamics (PD) of unaged FAFG, 7-day aged FAFG, and unaged synthetic glucagon was determined in octreotide-treated swine. Results: No fibrils were observed in TEM images of fresh or aged FAFG. Aged FAFG was 94% intact based on HPLC analysis and there was no loss of bioactivity. In the PD swine analysis, the rise over baseline of glucose with unaged FAFG, aged FAFG, and synthetic native glucagon (unmodified human sequence) was similar. Conclusions: After 7 days of aging at 37°C, an alkaline ferulic acid formulation of glucagon exhibited significantly less aggregation and degradation than that seen with native glucagon and was bioactive in vitro and in vivo. Thus, this formulation may be stable for 3-7 days in a portable pump for bihormonal closed-loop treatment of T1D.